Strategic and Operative Marketing Controlling - Noémi Hajdú (Theory, Methodology, Practice, 2013)
In uncertain economic situations, profit-seeking corporations work under constant pressure of efficiency. As a consequence, importance of evaluation is extending to such corporate areas, e.g. marketing which used to be fairly subjective, according to our past knowledge. Corporate leaders have recognized that successful corporate governance requires a system that analyses the efficiency of marketing activities. A new era is coming in the marketing profession when the effectiveness of marketing activity should be supported with specific figures. One of the evaluation methods is marketing controlling, which is widespread in the German speaking countries. This paper presents its theoretical framework and gives survey results on the use of strategic and operative methods in medium-sized and large companies in Hungary.